Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan Di Dinas Pemberdayaan Masyarakat Dan Desa Kabupaten Bogor - Heni Enjjelika; Widhi Ariyo Bimo; Hannisa Rahmaniar Hasnin (CV. ITTC INDONESIA, 2026)
Employee performance is an important factor in supporting organizational effectiveness, particularly in government institutions responsible for community empowerment and public services. The Department of Community and Village Empowerment of Bogor Regency is required to maintain professional, productive, and performance-oriented employees to support the success of village development programs. However, based on the pre-survey results, several problems were identified regarding compensation that was considered not fully aligned with employees’ workloads, as well as declining work motivation caused by limited appreciation and encouragement in the workplace. These conditions were assumed to affect employee performance. This study aims to examine and analyze the effect of compensation and work motivation on employee performance at the Department of Community and Village Empowerment of Bogor Regency, both partially and simultaneously. This research employed a quantitative approach using a survey method through questionnaire distribution to employees of the institution. The data analysis technique used was Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results showed that compensation and work motivation had a positive and significant effect on employee performance. Fair and appropriate compensation was proven to increase employee satisfaction and work enthusiasm, while high work motivation encouraged greater responsibility, discipline, and productivity. These findings contribute to the development of human resource management studies in the public sector, particularly regarding compensation and work motivation management in improving the performance of regional government employees. Therefore, this study concludes that improving employee performance can be achieved through effective and sustainable compensation and work motivation management. Future research is recommended to include other variables such as leadership, work environment, and organizational culture in order to obtain a more comprehensive understanding of the factors influencing employee performance.